2023
DOI: 10.3390/plants12091757
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antibacterial Activities of the Leaf and Stem Extracts of Combretum molle (R. Br. ex G. Don.) Engl. & Diels

Abstract: Medicinal plants offer reasonable and accessible alternatives to synthetic drugs and are often devoid of the adverse side effects, toxicity, and pathogenic resistance associated with synthetic medicine. Combretum molle has been utilized in African traditional medicinal practices and purportedly contains bioactive compounds with medicinally beneficial effects. This study investigated the hexane, chloroform, and methanol leaf and stem extracts for their antioxidant properties using the 2,2′-diphenyl-1-picrylhydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…The presence of phenolic hydroxyl groups having high protein binding affinity may halt microbial enzymes and simultaneously increase affinity to cytoplasmic membranes, thus increasing the antibacterial activity (Kurek-Górecka et al, 2013). Through the deactivation of enzyme activity, phenols result to cells enzymes pop off crash and also cell lysis (Parusnath et al, 2023). In the present study, the antibacterial activity observed from Combretum glatinusum leaf extracts might be attributed to the presence of this phytochemical.…”
Section: Ftir Analysis Of C Glutinusum Leaves and Barksmentioning
confidence: 51%
“…The presence of phenolic hydroxyl groups having high protein binding affinity may halt microbial enzymes and simultaneously increase affinity to cytoplasmic membranes, thus increasing the antibacterial activity (Kurek-Górecka et al, 2013). Through the deactivation of enzyme activity, phenols result to cells enzymes pop off crash and also cell lysis (Parusnath et al, 2023). In the present study, the antibacterial activity observed from Combretum glatinusum leaf extracts might be attributed to the presence of this phytochemical.…”
Section: Ftir Analysis Of C Glutinusum Leaves and Barksmentioning
confidence: 51%
“…Furthermore, there is evidence that antioxidant compounds, such as phenolics, flavonoids, alkaloids, fatty acids, tannins, terpenoids, and steroids are accountable for the antimicrobial activity of plant extracts [32,33]. Indeed, a variety of antioxidant metabolites, including flavonoids [19,34], terpenoids [19,35], and phenolic compounds [36], were reported in Cocos nucifera L. These compounds are well known to exert antimicrobial activity via a number of mechanisms, including bacterial or fungal membrane damage, inhibition of virulence factors (enzymes and toxins) and nucleic acid synthesis, leakage of cellular components, and inhibition and eradication of bacterial biofilm formation, among others [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%